1969
DOI: 10.1192/bjp.115.524.797
|View full text |Cite
|
Sign up to set email alerts
|

Emotional and Cognitive Changes in Pregnancy and Early Puerperium

Abstract: Emotional change during pregnancy and the postpartum period is very common (37, 42); mental illness of psychotic proportions occurs more frequently in the postpartum period than in the period of pregnancy (33). These psychotic illnesses occurring in the postpartum period have remained an area of controversy for several reasons. The clinical phenomenology of these psychotic reactions seems unusually rich in confusional and delirious features (19), even when reported by those who contend they are no different fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
1

Year Published

1985
1985
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(26 citation statements)
references
References 30 publications
3
22
1
Order By: Relevance
“…Yet there has been little investigation of perceived changes in cognition in the postpartum using the kind of simple self ratings typically used in studies of pregnancy. While Kane et al (1968) and Jarrahi-Zadeh et al (1969) asked postpartum women whether they had noticed any changes in memory, clarity of thought or concentration, the women were interviewed very soon after delivery (at only three days postpartum). Thus in Study 2, a group of women were asked to rate their cognitive abilities at two stages during pregnancy and again for a third time at six months postpartum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet there has been little investigation of perceived changes in cognition in the postpartum using the kind of simple self ratings typically used in studies of pregnancy. While Kane et al (1968) and Jarrahi-Zadeh et al (1969) asked postpartum women whether they had noticed any changes in memory, clarity of thought or concentration, the women were interviewed very soon after delivery (at only three days postpartum). Thus in Study 2, a group of women were asked to rate their cognitive abilities at two stages during pregnancy and again for a third time at six months postpartum.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of the first three aspects of cognition was motivated by the observation that these are cognitive functions in which pregnant women most commonly report changes (e.g. Brindle et al, 1991;Jarrahi-Zadeh et al, 1969;McDowell and Moriarty, 2000;Parsons and Redman, 1991;Poser et al, 1986), and the item relating to prospective memory was included to allow closer examination of the particular aspect of memory that might be affected.…”
Section: Introductionmentioning
confidence: 99%
“…For example, impairments on word list learning tasks have been observed during different trimesters and at postpartum (de Groot, Vuurman, Hormstra, & Jolles, 2006; Mickes, Wixted, Sha piro, & Scarff, 2009;Parsons et al, 2004). Furthermore, perfor mance on paragraph recall (Keenan, Yaldoo, Stress, Fuerst, & Ginsburg, 1998), planning (Jarrahi-Zadeh, Kane, Van De Castle, Lachenbruch, & Ewing, 1969), and cognitive speed tasks (Chris tensen, Leach, & Mackinnon, 2010) was worse only in the third trimester.…”
Section: Cihr Author Manuscriptmentioning
confidence: 99%
“…For example, impairments on word list learning tasks have been observed during different trimesters and at postpartum (de Groot, Vuurman, Hormstra, & Jolles, 2006; Mickes, Wixted, Sha piro, & Scarff, 2009;Parsons et al, 2004). Furthermore, perfor mance on paragraph recall (Keenan, Yaldoo, Stress, Fuerst, & Ginsburg, 1998), planning (Jarrahi-Zadeh, Kane, Van De Castle, Lachenbruch, & Ewing, 1969), and cognitive speed tasks (Chris tensen, Leach, & Mackinnon, 2010) was worse only in the third trimester.Others have failed to find any differences in scores on objective measures of cognitive functions during pregnancy and postpartum (Casey, 2000;Christensen, Poyser, Pollitt, & Cubis, 1999;Crawley, Dennison, & Carter, 2003;Harris, Deary, Harris Marlene, Lees, & Wilson, 1996;McDowall, 2000), even though participants often reported subjective cognitive difficulties (Christensen et al, 1999;Crawley et al, 2003;McDowall, 2000). It has been suggested that testing in a laboratory setting may underestimate the degree of impairment experienced in day-to-day life (Cuttler, Graf, Pawluski, & Galea, 2011;Rendell & Henry, 2008;).…”
mentioning
confidence: 99%
“…Finally, we wish to stress again the impor tant relationship between OCD and pregnan cy [1,2,[29][30][31]. The characteristics of OCD during pregnancy are of special interest, es pecially as they might involve frightening thoughts regarding the fetus.…”
Section: Discussionmentioning
confidence: 99%